Contrails from (A)ATSR(2) Data - Mannstein, Hermann; Büll, Rüdiger (ESA Publications Division, 2005)
The DLR contrail detection algorithm identifies linear contrails using the infrared split window channels of moderate resolution (~ 1km) satellite data. Within the ESA DUE project contrails this algorithm was adapted to ATSR2 and AATSR. Data from the years 1995, 2000 and 2004 is processed and evaluated for the North Atlantic and European region in order to retrieve information on occurence, extent and properties of linear contrails. First results are shown here.